The Implementation of Massive Open Online Courses (MOOCs)-Based E-Learning System for College Level Learners - Silvana, Hana; Hanoum, Nadia (Bina Nusantara University, 2017)
This research aimed to find out how the implementation of MOOCs-based e-learning system was as an attempt to provide equal access to education athigher education level in Indonesia and to describe the user profile of MOOCs based e-learning. This research used a descriptive quantitative method, and the subjects of the research were 30 MOOCs participants drawn randomly. The design of the MOOCs-based e-learning implementedhad following features. Those were a) Bahasa Indonesia content; b) responsive media interface that can be accessed from a variety of devices; c) the use of short duration video content to facilitate buffering process; d) the use of interactive multimedia content; e) the use of social learningprinciples through the feature of discussion forum; and f) the use of gamification principles through the provision of badges for participants. The results of this research indicate that MOOCs-based e-learning system has the potential to improve the equal access to higher education with severalindicators. First, the majority of participants are females. Second, the latest education of most users is high school or vocational high school. Last, most have been working as employees.